1973
DOI: 10.2307/1935671
|View full text |Cite
|
Sign up to set email alerts
|

Adaptational Biology and Energy Relationships of the Collared Peccary (Tayassu Tajacu)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Field and laboratory investigations were conducted to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…Life in arid and semiarid environments is a challenge to mammals because of the wide temperature ranges and associated water shortages. The collared peccary (17-35 kg) and the white-lipped peccary (25-40 kg) do not display the behavioral strategies commonly used by mammals to address these challenges in arid environments, such as digging holes and burying themselves, and/or tolerate direct sun exposure for prolonged periods because of their low thermal inertia (property associated with the body size) (Cain et al 2006;Zervanos and Hadley 1973). For these reasons, the collared peccary has been considered a model organism to study physiological and behavioral adaptations in arid environments over the past four decades (Gabor et al 1997;Sowls 1997;Zervanos 1975;Zervanos and Day 1977;Zervanos and Hadley 1973).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Life in arid and semiarid environments is a challenge to mammals because of the wide temperature ranges and associated water shortages. The collared peccary (17-35 kg) and the white-lipped peccary (25-40 kg) do not display the behavioral strategies commonly used by mammals to address these challenges in arid environments, such as digging holes and burying themselves, and/or tolerate direct sun exposure for prolonged periods because of their low thermal inertia (property associated with the body size) (Cain et al 2006;Zervanos and Hadley 1973). For these reasons, the collared peccary has been considered a model organism to study physiological and behavioral adaptations in arid environments over the past four decades (Gabor et al 1997;Sowls 1997;Zervanos 1975;Zervanos and Day 1977;Zervanos and Hadley 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Collared peccaries have many physiological characteristics that prevent dehydration, such as their ability to reduce water loss through evaporation and urination, and are capable of doubling their urine osmotic concentration (Zervanos and Hadley 1973). Studies using metabolic chambers demonstrated that this species has a narrow thermoneutral zone (TNZ, temperature range over which the animals maintain their basal metabolic rate without causing additional water loss) that ranges from 25°C (lower critical temperature) to 35°C (upper critical temperature).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite growing theoretical interest, few ecological studies have addressed behavioral thermoregulation in mammals (RusSELL, 1971;ZERVANOS & HADLEY, 1973;MORHARDT & GATES, 1974;INGRAM & LEGGE, 1971). Nevertheless, biophysical models (PORTER et al, 1973;PORTER & JAMES, 1979;BAKKEN, 1976;GATES, 1980;PORTER & TRACY, 1983) clearly demonstrate that small-scale microhabitat differences can significantly alter heat exchange and consequent metabolic energy costs.…”
Section: Introductionmentioning
confidence: 99%